THE APPLICATION OF INDIVIDUAL COUNSELING USING COGNITIVE RESTRUCTURING TECHNIQUES TO REDUCE STRESS IN CLIENT T, WHO IS PREGNANT OUT OF WEDLOCK - Amy Chintiea; Suryati Suryati; Hartika Utami Fitri (LP2M IAI Al-Khairat Pamekasan, 2025)
This research is entitled